Short-term social dynamics following anthropogenic and natural disturbances in a free-living mammal. (3rd June 2022) - Gall, Gabriella E C; Evans, Julian C; Silk, Matthew J; Ortiz-Jimenez, Chelsea A; Smith, Jennifer E
Abstract: Anthropogenic disturbances are widely recognized for their far-reaching consequences on the survival and reproduction of wildlife, but we understand comparatively little about their effects on the social lives of group-living animals. Here we examined these short-term changes in affiliative behavior as part of a long-term study on a human-tolerant and socially flexible population of California ground squirrels ( Otospermophilus beecheyi ). We used social network analysis to examine short-term changes in affiliative behavior and individual consistency in response to disturbances by humans, domestic dogs, or a natural predator (the coyote). Overall, juveniles were more involved than adults in affiliative interactions, but the short-term directional effects of these acute disturbances on social cohesion varied by disturbance type. Human and dog presence reduced aboveground connectivity, particularly for juveniles, whereas disturbances by coyotes generally promoted it. Beyond these effects, we also detected non-random responses to disturbances, though individuals were not very consistent in their directional response to different disturbance types. Our results demonstrate the flexible changes in social behavior triggered by short-term disturbances imposed by humans and other threats. More generally, our findings elucidate the underappreciated sensitivity of animal social interactions to short-term ecological disturbances, raising key questions about their consequences on the social lives of animals. Abstract : We studied the effect of potential threats on the social behavior of California ground squirrels. The presence of humans and dogs disrupted social cohesion, but coyotes promoted it. Our findings reveal the underappreciated effects of short-term perturbations on the social interactions of free-living animals. These findings have important implications for understanding the impacts of humans and other sources of disturbance on the social lives of animals living in nature reserves and parks.